Prediction of the unsteady turbulent flow in an axial compressor stage. Part 2: Analysis of unsteady RANS and LES data. (5th January 2015) - Gourdain, Nicolas
Highlights: Analysis of URANS and LES results in an axial compressor stage. Both LES and URANS show the role of passing wakes on transition. LES shows that relaminarization is possible on the stator suction side. LES predicts non-periodic oscillations related to the tip leakage flow. Abstract: This paper presents the analysis of URANS and LES database in a stage of an axial subsonic compressor. Details about numerical methods and comparison with experiments can be found in a companion paper. The analysis here focuses on the transition processes that take place in the rotor and stator rows. In the rotor, LES and URANS show that transition develops at mid-chord and is induced by the adverse pressure gradient. In the stator, the flow behavior is more complex since the transition is influenced by the rotor passing wakes, a laminar separation bubble on the suction side and the accumulation of rotor wakes on the pressure side. The analysis also investigates the unsteady flow patterns at the rotor/stator interface, from mid-span to the casing. In the tip region, LES shows the development of frequencies that are not correlated to the blade passing frequency, while URANS only predicts multiples of the blade passing frequency.